TDMA-Based Control Channel Access for IEEE 802.11p in VANETs. (5th August 2014) - Yang, Weidong; Liu, Wei; Li, Pan; Sun, Limin
Motivated by an efficient broadcast service in vehicular ad hoc networks (VANETs), we propose a TDMA-based channel access scheme for IEEE 802.11p control channel (CCH). The scheme reduces the rate of transmission collisions and improves the availability of time slots on the control channel by adjusting disjoint sets of time slots to vehicles moving in opposite directions and to the left and right slot frames. Further, the location information of a node is used to allocate the time slot, which efficiently decreases the rate of access collisions. Analysis and simulation results in city scenarios are presented to evaluate the performance of our scheme, which reduces significantly the transmission conflict and has shorter time delay than ADHOC and VeMAC.